PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI BADAN USAHA MILIK DESA (BUMDES) SE-KECAMATAN SUKASADA - I Dewa Gede Juni Artha Wira Wardhana; N. K. Sinarwati; F. Yudiatmaja (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to analyze the influence of motivation, work environment, and job satisfaction partially or simultaneously on the employee performance of BUMDes in the Sukasada District. Sample of this research is 101 employees with purposive sampling technique. The data collection technique uses a questionnaire that is distributed through the Google form which has fulfilled the validity and reliability tests. The data analysis technique used multiple linear regression analysis with the classical test which consisted of normality, multicollinearity, and heteroscedasticity tests which were then processed using SPSS. Hypothesis in research using the t test, F test, and the coefficient of determination (R2). The results showed that work motivation, work environment and job satisfaction partially have a significant effect on employee performance. The results of the F test state that motivation, work environment, and job satisfaction together have a significant effect on employee performance. The regression estimation results show that the predictive ability of all independent variables on employee performance is 65.7%, while 34.3% is influenced by other variables outside of this study.